Fetal malformation in a marmoset (Callithrix jacchus): case report - Ferraz, Myrna Campos [UNESP]; Matos, André V. R. [UNESP]; Prestes, Nereu Carlos [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Francelino, L. C. [UNESP]; Cunha, F. S. [UNESP]; Oba, Eunice [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
Callithrix jacchus is a neotropical primate adaptable in captivity. Colonies can be easily established in a short time and at low cost compared to other species of larger primates, which are normally used in laboratory. Because they are phylogenetically similar to humans in situations that induce anxiety, these small primates are increasingly being used in research involving the stress response. Wild animals in captivity are subjected to a series of stressful events that depending on the duration and intensity can modify the organic homeostasis. Observed in this study, serious problems occurred with the formation in fetal offspring of Callithrix jacchus kept in an environment with a high degree of stress.

O Callithrix jacchus é um primata neotropical de fácil adaptação em cativeiro. As colônias podem ser facilmente estabelecidas em um curto espaço de tempo e a um custo baixo comparado a outras espécies de primatas maiores, que são normalmente utilizados em laboratório. Por serem filogeneticamente semelhantes aos seres humanos em situações que induzem à ansiedade, esses pequenos primatas estão sendo cada vez mais utilizados em pesquisas que envolvam a resposta ao estresse. Animais silvestres em cativeiro estão submetidos a uma série de eventos estressores, os quais, dependendo da sua duração e intensidade, podem modificar a homeostase orgânica. Observaram-se, neste estudo, graves problemas ocorridos com a formação fetal nas proles de Callithrix jacchus mantidos em ambiente com alto grau de estresse.
Malformação fetal em sagui-de-tufo-branco (Callithrix jacchus): relato de caso
Keywords: Callithrix jacchus; estresse; cortisol; formação fetal; Callithrix jacchus; stress; cortisol; formation fetal